2015
DOI: 10.1038/nrneurol.2015.100
|View full text |Cite
|
Sign up to set email alerts
|

Is early-life iron exposure critical in neurodegeneration?

Abstract: The effects of iron deficiency are well documented, but relatively little is known about the long-term implications of iron overload during development. High levels of redox-active iron in the brain have been associated with neurodegenerative disorders, most notably Parkinson disease, yet a gradual increase in brain iron seems to be a feature of normal ageing. Increased brain iron levels might result from intake of infant formula that is excessively fortified with iron, thereby altering the trajectory of brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 138 publications
1
71
0
Order By: Relevance
“…This finding may place iron excess as a central component in neurodegenerative processes since many neurodegenerative disorders are accompanied by iron accumulation in brain regions. Moreover, indiscriminate iron supplementation to toddlers and infants, modeled here by iron overload in the neonatal period, has been considered a potential environmental risk factor for the development of neurodegenerative disorders later in life 52 . Our findings also strongly suggest that CBD has neuroprotective effects, at least in part by blocking iron-induced apoptosis even at later stages, following iron overload, which puts CBD as a potential therapeutic agent in the treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may place iron excess as a central component in neurodegenerative processes since many neurodegenerative disorders are accompanied by iron accumulation in brain regions. Moreover, indiscriminate iron supplementation to toddlers and infants, modeled here by iron overload in the neonatal period, has been considered a potential environmental risk factor for the development of neurodegenerative disorders later in life 52 . Our findings also strongly suggest that CBD has neuroprotective effects, at least in part by blocking iron-induced apoptosis even at later stages, following iron overload, which puts CBD as a potential therapeutic agent in the treatment of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that public recommendations for AD risk reduction should caution the use of iron supplementation for those whom it is not required [18,41,42]. Dietary patterns such as a Mediterranean diet and reduced red meat consumption that associate with lower AD risk do tend to have a low iron intake, but also have other unrelated health benefits for example high intake of vegetables and low saturated fat.…”
Section: Discussionmentioning
confidence: 99%
“…Iron has been implicated in disorders such as Parkinson's disorder and it may be the iron levels during development that are implicated. Iron levels in tooth enamel and dentine can be directly mapped to the source and timing of infant nutrition during development of the tooth, thus providing an opportunity to correlate this with neurodegenerative disorders [ 21 ]. This retrospective method is attractive for exploring past chemical exposure during the development years.…”
Section: The Oral Environment: a Model For Other Body Systemsmentioning
confidence: 99%